Medication rule and mechanism of traditional Chinese medicine in treating metabolism-associated fatty liver disease based on bioinformatics technology - Zhang Yunkun; Yao Rong; Li Lin; Li Wenli; Li Changqing; Pan Yu; Li Shunxiang (KeAi Communications Co., Ltd., 2023)
[Abstract]: [Objective]: To analyze the main syndrome types, medication rules, and core prescription characteristics of traditional Chinese medicine (TCM) in the treatment of metabolism-associated fatty liver disease (MAFLD), and to predict the anti-MAFLD mechanism of core formula, so as to provide references for the clinical application of TCM and the development of new drugs. [Methods]: Literature research on TCM in treating MAFLD was retrieved from China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), and Wanfang Database since the establishment of the database to July 2022. Excel 2019 and Chinese Medicine Inheritance Computing Platform (V3.0) were used for frequency analysis, association rule analysis, and cluster analysis of effective prescriptions. The key components, targets, and action pathways of anti-MAFLD core formulas were predicted by network pharmacology. Finally, the interactions between the obtained core components and their core targets were verified reversely by molecular docking technology. [Results]: A total of 218 articles were screened and selected, including 352 prescriptions, involving 270 traditional Chinese herbs. The drugs were used a total of 3 901 times, and a total of 10 915 cases were collected, among which the prevalence rate was higher in males. The main types of TCM syndrome included intermingled phlegm and blood stasis syndrome, liver depression and spleen deficiency syndrome, and damp-heat in liver and gallbladder syndrome, among which Shanzha (Crataegi Fructus), Danshen (Salviae Miltiorrhizae Radix et Rhizoma), Fuling (Poria), Zexie (Alismatis Rhizoma), Chaihu (Bupleuri Radix), and Baizhu (Atractylodis Macrocephalae Rhizoma) were the most frequently used. The properties of Chinese medicine primarily encompassed thermal characteristics, with a predominant emphasis on cold and warm; the flavors of herbs were predominantly characterized by bitterness and sweetness, while the majority exhibited tropism towards the spleen and liver meridians. The drugs were primarily classified based on their efficacy in tonifying deficiencies, promoting diuresis and moistening, enhancing blood circulation and removing blood stasis, heat-clearing, etc. The association rules were employed to derive a set of 20 core drug pairs, while cluster analysis was utilized to identify three distinct groups of core drug combinations. Network pharmacological showed that the main components of the core formula "Shanzha (Crataegi Fructus) - Danshen (Salviae Miltiorrhizae Radix et Rhizoma) - Zexie (Alismatis Rhizoma) - Chaihu (Bupleuri Radix) - Fuling (Poria)" in the treatment of MAFLD were quercetin, apigenin, puerarin, luteolin, ursolic acid, kaempferol, tanshinone IIA, emodin, paeonol, etc., which involved RAC-alpha serine/threonine-protein kinase 1 (AKT1), cellular tumor antigen p53 (TP53), interleukin (IL)-6, IL-1β, signal transducer and activator of transcription 3 (STAT3), epidermal growth factor receptor (EGFR), peroxisome proliferative activated receptor gamma (PPARG), and other key targets. The molecular docking results showed that the core components had good binding to lipid and atherosclerosis, and phosphatidylinositol 3 kinase (PI3K)/AKT signaling pathway-associated proteins. [Conclusion]: The main principles of TCM for the treatment of MAFLD involve soothing the liver and strengthening the spleen, eliminating phlegm and dampness, clearing heat and dampness, as well as promoting blood circulation and removing blood stasis. The core formula may exert anti-MAFLD effects mediated through multiple components, targets, and signaling pathways. This study establishes a theoretical foundation for the clinical application of TCM in the treatment of MAFLD, and serves as a reference for further exploration of new drugs against MAFLD.